2017
DOI: 10.1021/acs.biochem.7b00195
|View full text |Cite
|
Sign up to set email alerts
|

Structural Insight into the Stabilizing Effect of O-Glycosylation

Abstract: Protein glycosylation has been shown to have a variety of site-specific and glycan-specific effects, but so far, the molecular logic that leads to such observations has been elusive. Understanding the structural changes that occur and being able to correlate those with the physical properties of the glycopeptide are valuable steps toward being able to predict how specific glycosylation patterns will affect the stability of glycoproteins. By systematically comparing the structural features of the O-glycosylated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
22
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 58 publications
4
22
0
Order By: Relevance
“…Importantly, increased conformational rigidity, due to specific interactions between the O‐glycan and key amino acid residues in the protein sequence, seems to contribute significantly to the increased stability of certain glycoforms. This is supported by recent results from NMR studies on various homogeneous O‐glycoforms of CBM and by proteolytic stability assays and molecular dynamic simulation on a model of intrinsically disordered proteins . Taken together, these findings suggest a coevolution of the glycan protective motif with the adjacent amino acid composition.…”
Section: Effect On Stabilitysupporting
confidence: 73%
“…Importantly, increased conformational rigidity, due to specific interactions between the O‐glycan and key amino acid residues in the protein sequence, seems to contribute significantly to the increased stability of certain glycoforms. This is supported by recent results from NMR studies on various homogeneous O‐glycoforms of CBM and by proteolytic stability assays and molecular dynamic simulation on a model of intrinsically disordered proteins . Taken together, these findings suggest a coevolution of the glycan protective motif with the adjacent amino acid composition.…”
Section: Effect On Stabilitysupporting
confidence: 73%
“…Glycosylation of proteins is known to influence their structure 44 46 . In particular, the high levels of O-glycosylation typically seen in the serine and threonine-rich repetitive regions of mucins are known to confer extended, rod-like structures to these regions 44 , 45 , 47 . MUC2, a highly O-glycosylated intestinal mucin, has been shown to dimerize via a C-terminal cysteine knot domain, and then trimerize via N-terminal von Willebrand domains in a pH and Ca 2+ -dependent manner 17 , 48 , 49 .…”
Section: Discussionmentioning
confidence: 99%
“…Small differences in protein backbone flexibility and concomitant large differences in resistance to proteolysis were also recently found for a structured protein with a single attached glycan, α-mannose or α-glucose. 24 Chaffey et al suggested that a chain of specific interactions between O -mannosyl and side chains of close residues may be propagating stiffening along the protein backbone. The similar behavior observed with IDPs suggests that the effects of α-mannose on protein stiffening may not be exclusive to a specific protein fold.…”
mentioning
confidence: 99%